Increased Incidence of Pancreatic Steatosis Detected Using Computed Tomography at Initial Diagnosis of Coronavirus Disease 2019 - Öz, Ayşegül; Akçalar, Seray (Turkish Journal of Gastroenterology, 2023)
Background: It is known that hepatic steatosis, diabetes, obesity, and metabolic syndrome are poor prognostic criteria for coronavirus disease 2019. Closely associated with these factors, pancreatic steatosis has yet to be clarified regarding its incidence in patients with coronavirus disease 2019 and its effect on prognosis. This study aimed to compare the incidence of pancreatic steatosis detected in non-contrast chest computed tomography examinations of patients with coronavirus disease 2019 pneumonia at the time of diagnosis with that of the general population.Methods: In the present retrospective study, which included 399 patients, densities of 5 different regions of the pancreas and 4 different regions of the spleen were measured, and the mean value of the measured densities was obtained. The difference between the mean pancreatic attenuation and splenic attenuation was defined as pancreatic steatosis if pancreatic attenuation–splenic attenuation ≤−5.Results: The median pancreatic density in patients with coronavirus disease 2019 was significantly lower than in those who tested negative (P = .034). In patients who were coronavirus disease 2019 positive, the incidence of pancreatic steatosis was statistically significantly higher (54.3% vs. 43.0%, P = .031).Conclusions: According to the non-contrast chest computed tomography examination of the patients with coronavirus disease 2019 performed at the time of admission, the incidence of pancreatic steatosis was higher than that of the normal population of a similar age group. Given that patients with pancreatic steatosis and the accompanying metabolic syndrome are more prone to inflammation, the findings suggest that these patients underwent more chest computed tomography examinations at the time of diagnosis. Therefore, pancreatic steatosis may be a poor prognostic factor in coronavirus disease 2019.Cite this article as: Öz A, Akçalar S. Increased incidence of pancreatic steatosis detected using computed tomography at initial diagnosis of coronavirus disease 2019. Turk J Gastroenterol. 2023;34(3):270-277.